1971
DOI: 10.1002/qua.560050502
|View full text |Cite
|
Sign up to set email alerts
|

Increased‐valence formulae and the bonding of oxygen to haemoglobin

Abstract: AbstractsThe molecular orbital configuration for the ground-state of 0, generates the valence formula -0 -0 -. "Increased-valence" formulae for triatomic and polyatomic molecules have been developed recently. In them, more electrons participate in bonding than is possible for the familiar valence-bond formulae. Using oxyhaemoglobin as an example of an oxygen carrier, various increased-valence formulae are generated for the FeO, groups. In the low-energy formulae, the iron is bonded to the above valence formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Both are important in polarizing the Fe-O 2 π-bond. In previous studies on {FeNO} 6 , it was found that the degree of polarization is governed by the magnitude of the energy gap of the Fe-NO π-bonding and antibonding orbitals relative to the strength of the exchange interaction between electrons in these orbitals (44). When the energy gap is large relative to the exchange interaction, the bond remains unpolarized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both are important in polarizing the Fe-O 2 π-bond. In previous studies on {FeNO} 6 , it was found that the degree of polarization is governed by the magnitude of the energy gap of the Fe-NO π-bonding and antibonding orbitals relative to the strength of the exchange interaction between electrons in these orbitals (44). When the energy gap is large relative to the exchange interaction, the bond remains unpolarized.…”
Section: Discussionmentioning
confidence: 99%
“…The iron oxygen-binding proteins contain an S = 0 {FeO 2 } 8 active site, denoting eight valence electrons delocalized among the Fe 3d and O 2 π*-orbitals in the Enemark-Feltham (1) notation used for metal-NO complexes. Three electronic structure models have been proposed by Pauling and Coryell (2, 3) (low-spin Fe II with singlet O 2 ), Weiss (4) (low-spin Fe III antiferromagnetically coupled to doublet O 2 − ), and McClure (5), Harcourt (6,7), and Goddard and Olafson (8) (S = 1 Fe II antiferromagnetically coupled to triplet O 2 , also known as the "ozone" model). Much computational work has been done, with all three models supported by different calculations (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…The deoxygenated form of both proteins are high-spin Fe II , S = 2, and become diamagnetic upon dioxygen binding. Three possible descriptions of the spin singlet ground state of oxyhemoglobin are generally considered: a low spin (S=0) ferrous center with diamagnetic O 2 , as proposed by Pauling [72], a low-spin (S=1/2) ferric center antiferromagnetically coupled to a O 2 − doublet, as proposed by Weiss [73], and an intermediate (S=1) ferrous center antiferromagnetically coupled to an O 2 triplet as proposed by McClure [74], Harcout [75], and Goddard [76]. The sensitivity of L-edge absorption spectroscopy for probing electron delocalization was applied to shed new light on this long standing problem.…”
Section: L-edge Xasmentioning
confidence: 99%
“…8 The precise nature of the Fe–O 2 bonding has been contentious. In addition to the Pauling model with its singlet dioxygen, 6, 9 Weiss proposed the antiferromagnetically coupled model of Fe III ( S =1/2)–O 2 − ( S =1/2); 10 and the ozone model Fe II ( S =1)–O 2 ( S =1) of McClure, 11 Harcourt, 12, 13 and Goddard 14 has also been put forward. Of these models, the Pauling model is closest to that supported by current data.…”
Section: Introductionmentioning
confidence: 99%